Re-inventing Paulo Freire - Mariateresa Muraca (European Journal for Research on the Education and Learning of Adults, 2023)
The paper explores the importance of social movements as reinventors of Paulo Freire’s pedagogy and promoters of a radical popular education. It particularly focuses on the Movimento de Mulheres Camponesas (MMC) (Peasant Women’s Movement), which was founded in 2004 and is currently organised in eighteen Brazilian States. My reflections arise from a collaborative and multi-sited ethnography conducted with the Movement in the State of Santa Catarina, in the South of Brazil, between 2011 and 2015. In the light of this research, I will argue that the Freirean inspiration represents a path and a challenge for the MMC and is evident in its genealogy, struggles for education, political-educational methodologies and in the process of forming of militant subjectivities. On the other hand, I will argue that the Movement contributes to expanding Freire’s proposal to new themes, such as: feminist struggles and the environmental question.